A relativistic disc reflection model for 1H0419–577: Multi-epoch spectral analysis with XMM–Newton and NuSTAR. Issue 3 (28th November 2018) - Jiang (姜), Jiachen (嘉陈); Walton, Dominic J; Fabian, Andrew C; Parker, Michael L
ABSTRACT: We present a detailed analysis of the spectral properties of the Seyfert 1 galaxy 1H0419−577, based on the archival XMM–Newton, NuSTAR, and simultaneous Swift observations taken between 2002 and 2015. All the observations show a broad emission line feature at the iron band. We demonstrate that the broad-band spectral variability at different levels can be explained by the combination of light-bending effects in the vicinity of the central black hole plus a thin warm absorber. We obtain a black hole spin of a > 0.98 by fitting the multi-epoch spectra with the relativistic disc reflection model. 1H0419−577 is accreting at$40{{\ \rm per\ cent}}$ of its Eddington limit and its X-ray band shows the hardest power-law continuum in the highest flux state, which was previously more commonly seen in AGNs with a low accretion rate (e.g. L x / L Edd < 10 −2 ). The NuSTAR observation shows a cool coronal temperature of$kT=30^{+22}_{-7}$  keV in the high flux state.